Chapter Concepts of policy and political strategies of Great Britain and their transformations until 1956 - Bednarek, Zbigniew (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
This work analyzes the strategies and policies implemented by the United Kingdom in the colonial period that still have a significant impact on the internal situation of the country and its international relations (including the concepts deriving from liberalism and republicanism). Alongside British foreign policy (appeasement, phoney war), the paper discusses the distribution of political forces in Europe and in the world as well as London’s policy for Africa and the Balkans. Another object of study is Britain’s attitude towards the conflicts: the Polish-Bolshevik War, the Chinese crisis (1925–1928), Abyssinian conflict (1935–1936), World War II, the first Arab-Israeli War (1948–1949), and the Suez crisis (1956).